Analysis the Spread of Chlorophyll-A Concentration in Birah-Birahan Island Waters Using Landsat 8 Images - Rosdianto, Rosdianto; Kaharuddin, Kaharuddin; Rudiyanto, Rudiyanto (Sumatra Journal of Disaster, Geography and Geography Education, 2021)
ABSTRACT: Research aims to determine the value of concentration and spread profile of chlorophyll-a in Birah-birahan Island waters. To process the spread profile data of chlorophyll-a concentration in Birah-Birahan Island waters, the data were used is Landsat 8 imagery data in 2018, i.e. February and August and February and October in 2019, data processing uses the er-mapper and arcgis application by using the Pentury algorithm and Hanintyo algorithm. Information was obtained that the value of chlorophyll-a concentration used the pentury algorithm in 2018, February on west monsoon, i.e. 0.06 mg/m3 and August on east monsoon, i.e. 0.07 mg/m3, in 2019 February on west monsoon, namely 0.06 mg/m3 and October on east monsoon is 0.07 mg/m3 and chlorophyll-a concentration value using the Hanintyo algorithm in 2018 February on west monsoon i.e. 0.22 mg/m3 and August in the east monsoon is 0.27 mg/m3, in 2019 February on west monsoon i.e. 0.25 mg/m3 and October on east monsoon i.e. 0.24 mg/m3. It can be concluded that the concentration value by the pentury and Hanintyo algorithm of two different years in west and east monsoon the highest chlorophyll-a concentration value were known based on Hanintyo algorithm. Keywords: Chlorophyll-a, Landsat 8, Spread, Birah-Birahan Island.